2009
DOI: 10.1055/s-0030-1249654
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Cranial Nerves and Cauda Equina: An Emerging Magnetic Resonance Imaging Pattern in Metachromatic Leukodystrophy and Krabbe Disease

Abstract: We report on three cases of infantile Krabbe disease and one case of infantile metachromatic leukodystrophy showing magnetic resonance (MR) imaging findings of diffuse and coexistent cranial nerve and cauda equina nerve roots enhancement. Such findings may be simultaneous, or even precede, typical white matter abnormalities and, in the appropriate clinical context, may facilitate an earlier diagnosis. There is a rational for the use of contrast agents and craniospinal MR imaging during the first imaging of chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 10 publications
0
28
0
Order By: Relevance
“…Evidence for enlarged peripheral nerves in Krabbe disease can be found in prior MRI studies: Bilateral brachial plexus enlargement has been demonstrated in 2 patients with late‐onset Krabbe disease . Thickening and enhancement of cauda equine nerve roots has been described by quantitative and routine MRI . A diffuse symmetric enlargement of cranial nerves, most frequently of the optic nerves, has been shown .…”
Section: Discussionmentioning
confidence: 92%
“…Evidence for enlarged peripheral nerves in Krabbe disease can be found in prior MRI studies: Bilateral brachial plexus enlargement has been demonstrated in 2 patients with late‐onset Krabbe disease . Thickening and enhancement of cauda equine nerve roots has been described by quantitative and routine MRI . A diffuse symmetric enlargement of cranial nerves, most frequently of the optic nerves, has been shown .…”
Section: Discussionmentioning
confidence: 92%
“…Cranial nerve and cauda equina nerve root enhancement have also been reported in a 9‐month old infant with Cockayne syndrome . The enhancement is suggestive of blood‐nerve barrier breakdown . Altered vascular permeability due to perivascular inflammation or infiltration has been suggested as a possible pathogenetic mechanism in Krabbe disease .…”
Section: Neurometabolic Diseasesmentioning
confidence: 94%
“…Enhancing cranial nerves and cauda equina nerve roots have also been reported in pediatric patients with Krabbe disease and metachromatic leukodystrophy . The imaging findings in the spine might precede or present simultaneously with the white matter abnormalities in the brain, and determination of galactocerebroside β‐galactosidase and arylsulfatase A has been suggested in all children with unexplained cranial nerve and cauda equina nerve root enhancement .…”
Section: Neurometabolic Diseasesmentioning
confidence: 97%
See 2 more Smart Citations